Association of two polymorphisms rs3749117 and rs3749119 in PLA2R1 with idiopathic membranous nephropathy:A Meta-analysis - Sheng Qian; Jian Xun; Zhang Jing; Zhang Sheng-nan; Gao Zhan (Linchuang shenzangbing zazhi)
Objective To evaluate the relationship between two types of single nucleotide polymorphism（SNP）and idiopathic membranous nephropathy（IMN）.Methods A systematic search was performed in English databases of PubMed and Embase and Chinese databases of CNKI,WanFang and China Biology Medicine（CBM）on the susceptibility of rs3749117 and rs3749119 to IMN respectively.Odds ratio（OR）and 95% confidence interval（95%CI）were selected as the effect sizes.Through careful and rigorous preliminary screening and re-screening of the literature, the matching literatures were retrieved and Newcastle-Ottawa scale was utilized for literature evaluations.Then the relevant data were extracted and processed for Meta-analysis.Results Finally a total of 7 case-control studies were included.Six sets of original data examined the correlation between SNP rs3749117 and IMN susceptibility, including 1750 cases in case group and 1593 cases in control group.Through the analysis of 5 genetic models, rs3749117 was correlated with the susceptibility of Asian IMN.Based upon the eligible studies, the pathogenic gene was T [C/T:OR=0.528,95%CI（0.372-0.749）,P<0.001].The relationship existed between SNP rs3749119 and IMN susceptibility.Meta-analysis indicated that a significant correlation existed between rs3749119 and Asian IMN susceptibility.Also based upon current researches, gene C might be a pathogenic gene[C/T,OR=2.019（1.405-2.903）,P<0.001].Conclusion A distinct correlation exists between rs3749119/rs3749117 and Asian IMN susceptibility.And the pathogenic genes of rs3749119 and rs3749117 are C and T respectively.